A review of current knowledge regarding insulin resistance among the pediatric population - Wolnowska, Monika; Górnik-Horn, Karolina; Staśkiewicz, Wiktoria; Grajek, Mateusz (Journal of Education, Health and Sport, 2022)
One of the key roles in maintaining the body's homeostasis is played by insulin. The presence of insulin receptors in almost all cells of the body reflects the importance of this hormone. Insulin resistance is a state of impaired glucose homeostasis resulting from a decreased sensitivity of peripheral tissues to insulin, despite normal or elevated serum levels. The purpose of this paper is to present the current state of knowledge on the pathogenesis, risk factors, and diagnosis of insulin resistance at developmental age.